1969
DOI: 10.1161/01.cir.40.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Studies in Chronic Uremia

Abstract: Hemodynamic functions and blood volume were observed in patients with chronic uremia. Thirty-one patients had clinical features of circulatory congestion and 37 did not. The degree of anemia and acidosis was comparable in both groups. However, creatinine clearance was significantly lower in patients with circulatory congestion. Both groups of patients had greater blood pressure, heart rate, plasma volume, and total peripheral resistance than normal. Resting cardiac output was abnormally decreased in 19% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
4

Year Published

1972
1972
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(39 citation statements)
references
References 24 publications
2
33
0
4
Order By: Relevance
“…was found. This increase in heart rate agrees with other studies investigating hemodynamics during HD [4, 14, 15, 16]. …”
Section: Discussionsupporting
confidence: 92%
“…was found. This increase in heart rate agrees with other studies investigating hemodynamics during HD [4, 14, 15, 16]. …”
Section: Discussionsupporting
confidence: 92%
“…Measurement of cardiac output by indicator dye dilution or from plasma volume changes produced variable results (17,18). While Goss et al (7) reported a reduction in cardiac output, subsequent studies after hemodialysis by DelGreco et al (8) showed a fall in cardiac output in patients without congestive heart failure compared to an increased cardiac output in patients with associated congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier human studies of hemodynamic changes after hemodialysis in patients with chronic renal failure were confined to the demonstration of alterations in cardiac output, heart rate, systemic arterial pressure, and peripheral vascular resistance (7)(8)(9)(10)(11). The advent of noninvasive techniques has permitted a more comprehensive evaluation of left ventricular function in patients in chronic renal failure and of the effects of hemodialysis (12)(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Adanya perbedaan yang bermakna pada penelitian ini dikarenakan peningkatan cardiac output oleh beberapa mekanisme seperti penurunan volume overload cairan ekstraselular, penurunan resistensi vaskuler perifer, dan pengeluaran toksin uremik yang menjadi faktor cardiopressor. Hal tersebut sesuai dengan penelitian yang dilakukan oleh Del Greco et al (1969) mencatat bahwa, pada pasien PGK stadium V yang menjalani HD mengalami perubahan pada hemodinamik jantung salah satunya kinetik ventrikel kiri. Hal serupa juga dinyatakan oleh Mehta et al (1983) bahwa pemindahan toksin uremik dan stimulasi perubahan kalsium dan kalium dapat meningkatkan fungsi jantung.…”
Section: Pembahasanunclassified